The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1136/openhrt-2021-001914
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations leading to arrhythmogenic left ventricular cardiomyopathy

Abstract: ObjectivesTo describe a cohort of patients with arrhythmogenic left ventricular cardiomyopathy (ALVC), focusing on the spectrum of the clinical presentations.MethodsPatients were retrospectively evaluated between January 2012 and June 2020. Diagnosis was based on (1) ≥3 contiguous segments with subepicardial/midwall late gadolinium enhancement in the left ventricle (LV) at cardiac magnetic resonance plus a likely pathogenic/pathogenic arrhythmogenic cardiomyopathy (AC) associated genetic mutation and/or famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Of the remaining 35 articles, 23 were excluded as consisting of case reports, and 3 due to the presence of duplicate data in other selected papers of the same research group [ 6 , 7 , 17 ]. Overall, 9 papers were finally considered for this review ( Table 1 ) [ 5 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A PRISMA flow diagram depicts the flow of information through the different literature review phases ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 35 articles, 23 were excluded as consisting of case reports, and 3 due to the presence of duplicate data in other selected papers of the same research group [ 6 , 7 , 17 ]. Overall, 9 papers were finally considered for this review ( Table 1 ) [ 5 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. A PRISMA flow diagram depicts the flow of information through the different literature review phases ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…While in the last few years the possible role of inflammation in ACM onset and progression led to a significant number of publications, few detailed clinical studies on a large cohort of patients with “hot-phases” can be found [ 23 , 24 , 25 , 26 ]. We were able to select only 9 studies describing cohorts of patients affected with ACM who showed myocarditis-like episodes [ 5 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. This is probably due to the low prevalence of these episodes in the overall ACM population, and on the other hand, to the problem of differential diagnosis with acute myocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Casella et al (2020) evaluated a series of ALVC patients and among 12 with a positive genetic result found three DSG2 and 9 DSP genetic variant carriers [ 75 ]. Recently, Graziosi et al (2022) described a large series of ALVC patients and reported the presence of genetic variants of SCN5A and TMEM43 genes [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic spectrum of DSP cardiomyopathy is wide ( Table 1 ) [ 20 ]. The main clinical presentations include extensive subepicardial late gadolinium enhancement (LGE) on CMR, which is often disproportionate to the degree of LV dysfunction, in association with frequent premature ventricular contractions (PVC) and a propensity to life-threatening ventricular arrhythmias [ 9 , 17 , 18 , 19 ].…”
Section: Clinical Featuresmentioning
confidence: 99%